Exploration and Practice on Teaching Reform of Bilingual Courses in Finance - Zhang, Zheng; Pang, Huiyi; Wang, Wenxue (Transactions on Social Science, Education and Humanities Research, 2023)
In the bilingual teaching model of Chinese universities, the classroom teaching reform of financial courses seeks to integrate immersive education on the premise of meeting the requirements of the Ministry of Education to improve students' bilingual professional abilities and comprehensively evaluate student performance. However, the teaching reform of financial bilingual courses is also facing unprecedented development difficulties. Therefore, the article combines the actual classroom situation and the specific regulations of the Ministry of Education, sums up the experience and puts forward suggestions. The immersive teaching model inspires us: i) Cultivating students' learning ability and professional quality level is the core of education; ii) It is necessary to improve the practicality of bilingual courses; iii) Strengthen pre-service training for bilingual teachers is crucial.